Implementasi Sertifikasi Halal terhadap Pendapatan Pelaku Usaha Kripik Bintang Sembilan Di Bululawang - Wicahyono, Agus; Kuryanto, Asib Dwi; Salam, Abdus; Hasanah, Kemala (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2026)
The inclusion of a halal label on products significantly influences consumer trust, which in turn positively impacts company profits. Currently, some business actors perceive halal certification merely as a fulfillment of Islamic religious obligations, while a smaller portion recognize that halal certification can also enhance business revenue. This study aims to examine the benefits experienced by the owners of Bintang Sembilan Chips in Bululawang, a business operating in the food industry, after obtaining halal certification from the Indonesian Ulema Council (MUI), using Porter’s Value Chain approach. The data collected includes the value chain, general profile of the business owners, challenges encountered, and benefits gained after obtaining halal certification, which were obtained through questionnaires. The results indicate that implementing halal standards can increase the revenue of Bintang Sembilan Chips in Bululawang. This increase is attributed to enhanced consumer trust and purchasing interest in halal-certified products, the ability to access a broader market, and opportunities to participate in government-promoted programs. Based on the economic benefits observed, it can be concluded that possessing halal certification has a positive impact on the business owners’ income. Keywords: Business Revenue, Halal Certification, Business Owner